2015
DOI: 10.1016/j.nutres.2015.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between sulforaphane and selenium in protection against oxidative damage in colonic CCD841 cells

Abstract: 27Dietary isothiocyanates (ITCs) are potent inducers of the NF-E2-related factor-2 (Nrf2)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…To our knowledge, this study is the first to demonstrate DNA damage reduction and the modulation of Nrf2/ARE pathway by triterpenoids (both CDDO and TRF) in the normal cell line CCD841‐CoN. Although recent work reported that sulforaphane decreased H 2 O 2 ‐mediated oxidative damage and activated the Nrf2/ARE pathway in CCD841 cells, concentrations of 2.5–40 μM were required to elicit this effect. Triterpenoids have been reported to have other relevant bioactivities; oleanolic acid glycosides influence GI transit in mice ; triterpenoids modulate intestinal transport ; purified triterpenoids from Rubus parvifolius , including suavissimoside R1 and coreanoside F1, have antifatigue effects in mice and TRFs from Korean raspberries have potent anti‐inflammatory effects .…”
Section: Discussionmentioning
confidence: 71%
“…To our knowledge, this study is the first to demonstrate DNA damage reduction and the modulation of Nrf2/ARE pathway by triterpenoids (both CDDO and TRF) in the normal cell line CCD841‐CoN. Although recent work reported that sulforaphane decreased H 2 O 2 ‐mediated oxidative damage and activated the Nrf2/ARE pathway in CCD841 cells, concentrations of 2.5–40 μM were required to elicit this effect. Triterpenoids have been reported to have other relevant bioactivities; oleanolic acid glycosides influence GI transit in mice ; triterpenoids modulate intestinal transport ; purified triterpenoids from Rubus parvifolius , including suavissimoside R1 and coreanoside F1, have antifatigue effects in mice and TRFs from Korean raspberries have potent anti‐inflammatory effects .…”
Section: Discussionmentioning
confidence: 71%
“…We and others previously showed that Se and dietary phytochemical sulforaphane could synergistically induce TrxR1 through Nrf2 pathway in vitro [19], [20], [21]. This suggests that the interaction of dietary constituents could significantly alter the cellular redox traits.…”
Section: Introductionmentioning
confidence: 76%
“…The effects of SFN on non-transformed T-lymphocytes were similar to those recorded on Jurkat T-leukaemia cells 30 . SFN showed broad and complex effects on DNA methylation profiles in both normal and cancerous prostate epithelial cells 31 and regulated the Nrf2/ARE signalling pathway differently in human untransformed epithelial colon cells when compared to colorectal cancer cells 32,33 . Negrette-Guzman et al demonstrated SFN modulates mitochondrial dynamics differentially in normal and cancer cells 34 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%